Quantitative strength testing in ALS clinical trials. (9th August 2016) - Shefner, Jeremy M.; Liu, Dawei; Leitner, Melanie L.; Schoenfeld, David; Johns, Donald R.; Ferguson, Toby; Cudkowicz, Merit
Abstract : Objective: To study the attributes of quantitative strength testing using hand-held dynamometry (HHD) as an efficacy measure in 2 large phase 3 amyotrophic lateral sclerosis (ALS) trials. Methods: In the phase 3 trials of ceftriaxone and dexpramipexole, 513 and 943 patients, respectively, were enrolled in double-blind, randomized, placebo-controlled trials with planned follow-up of at least 1 year. Patients were studied every 3 months in the ceftriaxone study and every 2 months in the dexpramipexole study. Evaluators of HHD were trained and had to show evidence of adequate performance of strength testing; the testing paradigm involved testing 9 muscle groups in the upper and lower extremity bilaterally. Neither drug significantly affected any outcome measure. Strength measurements were evaluated by individual muscle and by megascores, which averaged scaled strength measures to produce an overall measure of muscle strength. Results: A measure combining rate of decline with both within- and between-patient variabilities of measurement, the coefficient of variation for rate of change, was calculated, and showed that HHD overall performed slightly less well than Amyotrophic Lateral Sclerosis Functional Rating Scale–revised (ALSFRS-R) but better than vital capacity. Individual muscles were highly correlated to the identical muscles on the contralateral side, as well as to other muscles in the same body region. Strength decline was correlated both with ALSFRS-R and vital capacity. Conclusion: Quantitative strength testing using HHD is a reliable and reproducible measure of decline in ALS.